Little witches. 1, Magic in Concord - Dragoon, Leigh, 1976- (Oni Press, 2020)
Meg, Jo, Beth, and Amy March, four sisters in nineteenth-century New England, secretly learn the family trade of witchcraft from their mother as Mr. Laurence, a witchfinder, moves next door with his grandson Laurie.